Employability Readiness Among Vocational College Students (Refrigeration and Air Conditioning Technology Courses) in The Southern Zone of Malaysia - Omar, Nur Faizah; Mohd Faiz, Nur Sofurah (Research and Innovation in Technical and Vocational Education and Training, 2022)
The readiness of prospective graduates to face the world of work is important to prevent prospective graduates from experiencing culture shock when entering the world of work. In general, this study aims to determine the employability readiness of vocational college students, especially final year students from the Refrigeration and Air Conditioning Technology Courses. This study involved 103 respondents from 9 vocational colleges in the southern zone by using a set of questionnaires as the research instrument. The value of the reliability index of the questionnaire items was 0.931. The results of the study were then analyzed by obtaining mean values, standard deviations, frequencies and percentages based on the data that had been processed. The results of the study showed that the employability readiness of vocational college students based on aspects of intellectual resources, personality resources, meta -skills resources and job -specific resources were at a high level, the mean score was between 4.00 to 4.5 out of a total score of 5.0. The findings of the study also found that there was a difference in employability readiness according to gender where male students were more prepared than female students at α = 0.05. In conclusion, vocational college students were at high level of readiness to face the world of work based on aspects of intellectual resources, personality resources, meta -skills resources and job -specific resources. This study showed that the government's goal to produce skilled and semi -skilled workforce of vocational college students was somewhat achievable. In addition, this study provided recommendations to certain parties so that they could take according actions in addition to ensuring that these students can meet their career goals.